Neural crest delamination and migration: Looking forward to the next 150 years. Issue 6 (20th April 2018) - Gouignard, Nadège; Andrieu, Cyril; Theveneau, Eric
Summary: Neural crest (NC) cells were described for the first time in 1868 by Wilhelm His. Since then, this amazing population of migratory stem cells has been intensively studied. It took a century to fully unravel their incredible abilities to contribute to nearly every organ of the body. Yet, our understanding of the cell and molecular mechanisms controlling their migration is far from complete. In this review, we summarize the current knowledge on epithelial‐mesenchymal transition and collective behavior of NC cells and propose further stops at which the NC train might be calling in the near future.